Hybrid thermochromic material - Zhou, Yang (2015)
Vanadium dioxide (VO2) is a key material for thermochromic applications, which has a great potential to respond to the environmental temperature changing due to metal-to-insulator (MIT) transition. Temperature response hydrogel is one of the organic thermochromic materials, which reversibly changes between a transparent and translucent state depending on temperature change. The application of PNIPAm hydrogel thin film for thermochromic smart windows has been investigated for the first time. With increasing thickness of hydrogel from 26 to 200 μm and increasing testing temperature from 20 °C to 60 °C, the solar modulating ability (ΔTsol) increases and the luminous transmittance (Tlum) decreases. Compared with the best reported result of the most studied inorganic VO2 thermochromic coatings, an unprecedented good combination of near doubled averaged Tlum (70.7% v.s 42.8%), higher ΔTsol (25.5% v.s 22.3%1) and lower transition temperature (~32 °C v.s ~68 °C) could be achieved by hydrogel with optimized thickness. Good durability and reversibility were established on proper sealing of the sandwich structure, thereby achieving a new milestone in the research for organic thermochromic materials. Due to the great thermochromic performance of PNIPAm hydrogel, a new generation of composite thermochromic material which integrates hydrogel with VO2 nanoparticles has been investigated and a dramatic enhancement of solar modulation has been observed. Our experimental data of VO2/hydrogel nanocomposite showed an unprecedented combination of thermochromic properties with solar modulation ability of 34.7%, which is much higher than the best report data 22.3% and at the same time, a comparable high average Tlum of 61.1% can be achieved. The combination of vanadium dioxide nanoparticles and hydrogel could offer large transmission contrast both in luminous and infrared range resulting largely enhanced overall solar modulation and the hybrid system opens a new avenue of thermochromic materials.